2020
DOI: 10.30831/akukeg.776415
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Validity of Teaching Efficacy on Task-Centered Anxiety: A Study on Physical Education Teacher Candidates

Abstract: This study aimed to determine the relationship between physical education teacher candidates' teaching efficacy and task-centered anxieties. Correlation survey model was used in this research. The research group consisted of 228 prospective physical education teachers, 84 of whom were female (37%) and 144 were male (63%), who were educated in the 3rd and 4th grades in 5 different universities. Personal information form, Teacher Occupational Anxiety Scale and Physical Education Teaching Efficacy Scale were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…err is called cross entropy, and J (W, (b) is the loss function; for good (W, (b) parameters, the loss function can be made to obtain a smaller value. The specific operation method is to achieve corresponding matrix norm F through the loss function Add regular term ( W ) [ 26 , 27 ]. Therefore, the final and complete loss function formula is as follows: …”
Section: Deep Transfer Learning Algorithms and Applicationsmentioning
confidence: 99%
“…err is called cross entropy, and J (W, (b) is the loss function; for good (W, (b) parameters, the loss function can be made to obtain a smaller value. The specific operation method is to achieve corresponding matrix norm F through the loss function Add regular term ( W ) [ 26 , 27 ]. Therefore, the final and complete loss function formula is as follows: …”
Section: Deep Transfer Learning Algorithms and Applicationsmentioning
confidence: 99%
“…It is mainly selected and set from the following angles. One is to measure and evaluate specific sports events, focusing on the students' mastery of skills in relevant sports events, which is mainly related to the content of physical education teaching; second, from the perspective of extracurricular exercise, focus on the evaluation of students' physical exercise habits, mainly related to extracurricular training; the third is to dynamically track the growth of students' physical and mental quality by introducing intelligent technology from the perspective of sustainable growth; fourth, starting from the situation of sports literacy, focus on the evaluation of students' sports character, collective sense of honor, and so on [22][23][24]. e setting of physical education curriculum learning evaluation indicators should be considered from the perspectives of theoretical basis, experience reference, basic ideas, and construction strategies.…”
Section: Evaluation Index Of Long Jump Training Coursementioning
confidence: 99%
“…From the perspective of data analysis, the content of this part is not included in the total score of the questionnaire. In the teaching quality evaluation questionnaire, the answer options of some questions involve very consistent (81-100), consistent (61-80), generally consistent (41-60), inconsistent (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and very inconsistent (0-20).…”
Section: Experimental Testmentioning
confidence: 99%
“…The concept of teaching efficacy refers to teachers' personal beliefs about their capability that they could influence students' performance (Xie et al, 2022). Researchers have found that teaching efficacy affects teachers' job satisfaction (Collie et al, 2012), classroom management (Tsouloupas et al, 2010), teaching-learning conceptions (Erbas, 2021), and taskcentered anxiety levels (Erbas and Ünlü, 2020); additionally, scholars have showcased its important role in helping students to realize their development potential (Pendergast et al, 2011). At present, questions pertaining to which factors can influence teachers' teaching efficacy have become the focus of global attention.…”
Section: Introductionmentioning
confidence: 99%